Prognostic factors and patterns of failure after surgery for T4 rectal cancer in the beyond total mesorectal excision era. Issue 12 (24th July 2019) - Peacock, O; Waters, P S; Bressel, M; Lynch, A C; Wakeman, C; Eglinton, T; Koh, C E; Lee, P J; Austin, K K; Warrier, S K; Solomon, M J; Frizelle, F A; et al.
Abstract: Background: Despite advances in the rates of total mesorectal excision (TME) for rectal cancer surgery, decreased local recurrence rates and increased 5-year survival, there still exists large variation in the quality of treatment received. Up to 30 per cent of rectal cancers are locally advanced at presentation and approximately 5–10 per cent still breach the mesorectal plane and invade adjacent structures despite neoadjuvant therapy. With the evolution of extended resections for rectal cancers beyond the TME plane, proponents advocate that these resections should be performed only in specialist centres. The aim was to assess the prognostic factors and patterns of failure after beyond TME surgery for T4 rectal cancers. Methods: Data were collected from prospective databases at three high-volume institutions specializing in beyond TME surgery for T4 rectal cancers between 1990 and 2013. The primary outcome measures were overall survival, local recurrence and patterns of first failure. Results: Three hundred and sixty patients were identified. The negative resection margin (R0) rate was 82·8 per cent (298 patients) and the local recurrence rate was 12·5 per cent (45 patients). The type of surgical procedure (Hartmann's: hazard ratio (HR) 4·49, 95 per cent c.i. 1·99 to 10·14; P = 0·002) and lymphovascular invasion (HR 2·02, 1·08 to 3·77; P = 0·032) were independent predictors of local recurrence. The 5-year overall survival rate for all patients was 61 (95 per cent c.i. 55 to 67) per cent. The 5-year cumulative incidence of first failure was 8 per cent for local recurrence, 6 per cent for local and distant disease, and 18 per cent for distant disease. Conclusion: This study has demonstrated that a coordinated approach in specialist centres for beyond TME surgery can offer good oncological and long-term survival in patients with T4 rectal cancers. Graphical Abstract: The aim was to assess the prognostic outcomes and patterns of failure after beyond total mesorectal excision (TME) surgery for T4 rectal cancers. A total of 360 patients from three specialist centres were evaluated; the negative resection margin was 82·8 per cent and the local recurrence rate was 12·5 per cent. This study demonstrates that a coordinated approach in specialist centres for beyond TME surgery can offer good oncological and long-term survival in patients with T4 rectal cancers. RT, radiotherapy. Beyond TME improves outcome